Exogenous 24‐epibrassinolide activates detoxification enzymes to promote degradation of boscalid in cherry tomatoes. (16th October 2020) - Yang, Yajie; Mao, Linchun; Guan, Weiliang; Wei, Xiaobo; Shao, Yelin; Luo, Zisheng; Lin, Xingyu; Li, Li
Abstract: BACKGROUND: Boscalid is often used to extend the storage time of postharvest cherry tomato. Pesticide residue has become an issue of food safety. This study sought to investigate the spatial distribution of boscalid residue in cherry tomato fruits and to determine the effect of 24‐epibrassinolide (EBR) in promoting boscalid degradation. RESULTS: Boscalid could quickly penetrate into cherry tomatoes, but mainly remained in the peel. The migration of boscalid from the peel into the core was a time‐consuming and complex process during storage. After 72 h, boscalid residues in the pulp and the core began to accumulate gradually. The exogenous application of EBR activated peroxidase, glutathione reductase and glutathione S ‐transferase, and effectively promoted the degradation of boscalid by a maximum decrease of 44.8% in peel, 54.0% in pulp and 71.2% in core. CONCLUSION: As one of the common pesticides, boscalid had a strong ability to enter the cherry tomato and thus become a potential risk for public consumption. Therefore, rational use of pesticides is recommended. The results of this study indicate that the possible risk of boscalid residue could be alleviated by EBR pretreatment through activating detoxification enzymes. © 2020 Society of Chemical Industry